Estudo da Supercondutividade Exótica: sistemas de multibandas - Padilha, Igor Tavares (2010)
Multi-band systems such as inter-metallic and heavy fermion compounds have quase-particles arising from different orbitals at their Fermi surface. Since these quase-particles have di®erent masses or densities, there is a natural mismatch of the Fermi wave vectors associated with different orbitals. This makes these materials potential candidates to observe exotic superconducting phases as Sarma or FFLO phases, even in the absence of an external magnetic field. The distinct orbitals coexisting at the Fermi surface are generally hybridized and their degree of mixing can be controlled by external pressure. In this work, we consider the problem of fermionic quase-particles that can transmute one into another with their total number conserved. We use a mean field approximation in weak coupling regime to study superconduc-tivity in two-band metallic systems with inter and intra-band interactions. Tuning the hybridization between the bands varies the mismatch of the Fermi wave vectors and produces different instabilities. For inter-band attractive interactions, we find a first-order normal-superconductor transition and a homogeneous metastable phase with gapless excitations, however it changes suddenly in presence of temperature since the order of the transition changes. In the case of intra-band interactions, the transition from the superconductor to the normal state is continuous as hybridization increases and associated with a quantum critical point. Besides, we investigate the existence of an FFLO type of phase in a two-band BCS superconductor controlled by hybridization. At zero temperature, as hybridization (pressure) increases we find that the BCS state becomes unstable with respect to an inhomogeneous superconducting state characterized by a single wave vector q. At non-zero temperature, the system has a BCS - Normal and FFLO - Normal second order phase transition and a BCS - FFLO first order phase transition, with the existence of a bicritical point.